2021년 3월 YES-AQ 기간 중 선박과 항공기로 관측한 서해상 황사 특성 - 김정은(Jeong Eun Kim); 정원석(Won Seok Jung); 서원익(Wonick Seo); 이선란(Shanlan Li); 오상민(Sang Min Oh); 신대근(Daegeun Shin); 고희정(Hee-Jung Ko); 유희정(Hee-Jung Yoo); 정주용(Chu-Yong Chung); 김연희(Yeon-Hee Kim) (한국대기환경학회지(국문), 2022)
The meteorological and aerosol characteristics of heavy dust during the 2021 YES-AQ campaign were analyzed. The source region of Asian Dust were sufficiently warm and dry, which is a proper condition for dust particles to be well intruded from the surface into the air above. Asian dust transported to the Shandong peninsula in China by the northwesterly, and then flowed into the Korean peninsula by the westerly. When the fine-mode aerosol is dominated in the period before arrival of Asian dust, scattering mass efficiency of PM10 was 5.3 m2/g and secondary pollutants such as sulfate, nitrate, and ammonium accountd for 50% of the total PM10 mass concentration. During the heavy dust period, PM10 mass concentration was maintained at 676~1,384 μg/m3 for about 24 hours from 21 KST on March 29, 2021 which is 25 times higher than the PM10 mass concentration before the Asian dust arrived. The light absorption coefficient in the heavy dust period was 38.5±9.4 Mm-1, which was higher than in the period before the arrival of Asian dust (22.5±10.2 Mm-1) confirming the Asian dust was highly absorbing. The scattering Ångström exponent and absorption Ångström exponent were 0.29 and 2.64, respectively, which are similar to the values reported around the Asian Dust source region. Although the concentration of fine particles did not increase during HD, it is presumed that the Asian Dust and fine particles were combined as the concentration of ions of anthropogenic pollutants increased to 15 μg/m3. Aerosol physical and optical properties were observed at 0.5~5.0 km over the Yellow Sea using an aircraft during HD. The coarse particle concentration and light scattering coefficient (545.7 Mm-1) and the light absorption coefficient (23.1 Mm-1) were the highest at the altitude of 0.9 km (36.5°N, 124.4°E). The scattering Ångström exponent (-0.067±0.13) and the absorption Ångström exponent (1.3~1.9) showed distinct characteristics of dust. The vertical lapse rate of the temperature from the aircraft and the backward trajectory analysis declared that the air origins were different below and over the altitude of 1.8 km. KCI Citation Count: 0